Mechanical properties of 3D printed PLA/fish scales hydroxyapatite composite for biomedical applications - Jaafar, Che Nor Aiza; Ismail, Muhammad Izham; Zainol, Ismail; Narthan, Mani Raj (Professional Association in Modern Manufacturing Technologies, 2024)
Researchers around the world are currently still investigating the possibility of using poly(lactic acid) (PLA)/hydroxyapatite (HAp) composite as a biomaterial. However, most of the research published utilized synthetically derived hydroxyapatite (HAp) which is more expensive than natural-based HAp. Hence, this project aims to investigate the reliability in terms of mechanical properties of the PLA/fish scales derived HAp (FsHAp) biocomposite comprised of PLA and FsHAp as a filler at various compositions ranging from 10 to 40 wt%. The PLA/FsHAp composite filaments were developed through melt blending of PLA resin and FsHAp powder by a twin screw extruder. The test specimen was prepared by 3D printing of composite filament using a Creality CR 6-SE 3D printer. However, the composite with filler content above 30 % failed to convert into filament due to the inherent brittleness of PLA/FsHAp composite. Hence, the mechanical properties were only analyzed for PLA, 10 and 20 wt% of PLA/FsHAp composites. The 20 wt% FsHAp filler content displayed higher tensile and flexural properties than 10 wt% despite the reduction in impact properties. In this study, the 20 wt% also indicates a better dispersion and reinforcing effect of the FsHAp filler on the PLA matrix. Overall results concluded that the addition of natural FsHAp fillers has a direct influence on the mechanical properties of PLA/FsHAp composite with the support of FTIR and SEM analysis. The composite has the potential to be used in the fabrication of medical device implants using 3D printing technique.